Altemeier Procedure for Complete Rectal Prolapse: An Operation for all Ages and its Long-Term Functional Outcomes - Thamarai Kannan Murugesan; Karthikeyan Srinivasan; Sastha Ahanatha Pillai; Villalan Ramasamy; Krishna Prasad Chowdary Mikkilineni Bharani; Venkkatesh Sreepathi; Padmanabhan Subbareddiar (Journal of Coloproctology)
Objective The aim of this study is to evaluate the long-term functional outcomes in patients treated by Altemeier's procedure for complete rectal prolapse.